Electrooxidation of methane to acetic acid over ZnO nanosheets: Defect-sites engineering. Issue 2 (April 2023) - Luo, Mingming; Li, Jiayao; Wang, Meiling; Ma, Yongqing; Zheng, Ganhong; Wang, Min; Zhou, Yitong
Abstract: Electrocatalytic conversion of methane (CH4 ) into high-valued liquid products have been studied extensively, yet still limited by their low product yields. Herein, we report the electrocatalytic conversion of CH4 into CH3 COOH in HCO3 - -contained electrolyte. By optimizing the surface-active sites via defects engineering, a high CH3 COOH yield of 347.31 mmol gcat −1 h −1, accompanied with a CH3 COOH selectivity of 85.4 %, was obtained at 1.3 V vs RHE over the optimal catalyst. This CH3 COOH yield is 2–5 orders of magnitude to previous reports so far as we know. Combinations of DFT theoretical simulation, defect sites characterization and control experiments of CH4 electrochemical conversion confirmed the important roles of ample surface Zn/O defects. Our work provides a new insight into the design of highly active and selective catalysts toward CH4 electrocatalytic conversion into CH3 COOH. Highlights: ZnO nanosheets with plenty of atomic defects were synthesized. They were used for highly efficient CH4 conversion to acetic acid. High yield rate and selectivity of 3473115 μmol (gcat h) −1 and 85.4 % are achieved. The electrocatalytic performance outperforms the previous reports as we know. Roles of Zn/O atom defects were studied in detail.